The Impact Of Demographic Characteristics On Visitors’ Movement And Congestion Inan Urban Public Park - Saeed, Bassma Abdul Nafaa (2020)
The main aim of this study is to investigate the visitors’ movement behaviour inside an urban public park. To achieve the aim, this study has sub-objectives: 1) To identify the demographic characteristics of urban public park visitors, the activities undertaken, and time spent inside the park. 2) To identify the congested and neglected paths based on the visitors’ selection and random movements inside the park. 3) To examine the relationship between the demographic characteristics of an urban public park visitors, paths, and movement patterns inside the park. 4) To forward recommendations regarding the visitors’ movement behaviour, which helps conserve the park environment and create a positive recreation experience. The study was conducted at Youth Park in Penang Island, Malaysia (called Taman Perbandaran Pulau Pinang-Malaysia).